De-biasing on university campuses in the age of misinformation. Issue 1 (16th December 2019) - Krutkowski, Sebastian; Taylor-Harman, Sarah; Gupta, Kat
Abstract : Purpose: The purpose of this study is to highlight that in today's polarised information environment, freedom of speech should not be conflated with a freedom to spread demonstrable lies unchallenged. The authors argue for a review of information literacy instruction to focus on social justice and help participants understand the implications of the views they may hold on vulnerable minority groups. Design/methodology/approach: In this paper, the authors review and reflect upon the delivery of staff development training on the facts and myths surrounding transgender issues. The authors also encourage other library and information professionals to expand their information literacy instruction into polarised issues that are marked by considerable amounts of misinformation. Findings: Training participants reported that being more aware of transphobic media coverage will help them reduce bias and better support trans students and staff. It also enabled further opportunities for colleagues across teams and a variety of roles to incorporate the principles of equality, diversity and inclusion into their practice. The success of the sessions also contributed to wider institutional change. Originality/value: Trans people are a vulnerable minority facing severe, persistent harassment and discrimination both in everyday life and potentially in educational settings. Offering staff effective tools to educate themselves about media transphobia is a step towards creating an environment where trans students and staff can flourish. The authors explore how the media coverage of trans issues allows misinformation to stick and spread. Through applying the concepts of critical thinking and information literacy to trans issues, the authors explain how unconscious bias towards the trans community can be challenged.